Telemedicine for Stroke: Quantifying the Long-Term National Costs and Health Benefits - Gao, Lan; Tan, Elise; Kim, Joosup; Bladin, Christopher F.; Dewey, Helen M.; Bagot, Kathleen L.; Cadilhac, Dominique A.; Moodie, Marj (Frontiers in Neurology, 2022)
Objectives Few countries have established national programs to maximise access and reduce operational overheads. We aimed to use patient-level data up to 12-months to model the potential long-term costs and health benefits attributable to implementing such a program for Australia. Methods A Markov model was created for Australia with an inception population of 10,000 people with stroke presenting to non-urban or suburban hospitals without stroke medical specialists that could receive stroke telemedicine under a national program. Seven Markov states represented the seven modified Rankin Scale (mRS) scores (0 no disability to 6 dead) plus an absorbing state for all other causes of death. The literature informed data for the model; and for the telemedicine program (including program costs and effectiveness) and patients these were extrapolated from the Victorian Stroke Telemedicine (VST) program with the initial status of patients being their health state at day 365 as determined by their mRS score study. Costs (2018 Australian dollars, healthcare, nonmedical, and nursing home) and benefits were reported for both societal and health care perspectives for up to a 25-year (lifetime) time horizon. Results We assumed 4,997 to 12,578 ischemic strokes would arrive within 4.5 hours of symptom onset at regional hospitals in 2018. The average per person lifetime costs were $126,461 and $127,987 from a societal perspective or $76,680 and $75,901 from a healthcare system perspective, and benefits were 4.43 QALYs and 3.98 QALYs gained respectively for the stroke telemedicine program and practice without such program. Stroke telemedicine program was associated with a cost saving of $1,526 (from the societal perspective) or an additional $779 (from the healthcare system perspective) and an additional 0.45 QALY gained per patient over the lifetime. The incremental costs of the stroke telemedicine program ($2,959) and management post stroke ($813) were offset by cost savings from rehospitalisation (-$552), nursing home care (-$2178), and nonmedical resource use (-$128). Conclusions The findings from this long-term model provide evidence to support ongoing funding for stroke telemedicine services in Australia. Our estimates are conservative since other benefits of the service outside the use of intravenous thrombolysis were not included.